Success factors model of special financial institution for Malay Reserve Land (MRL) development / Siti Hasniza Rosman, Abdul Hadi Nawawi and Rohayu Ab Majid - Rosman, Siti Hasniza; Nawawi, Abdul Hadi; Ab Majid, Rohayu (Faculty of Business and Management, 2022)
Malay Reserve Land (MRL) in Malaysia has a great potential to be developed successfully. However, the development is still lagging behind due to financial constraints. Currently, there are no specific funds provided to assist Bumiputera developers or owners to develop MRL comprehensively. Thus, the establishment of special financial institutions can drive the development of MRL. However, the special financial institutions need to fulfill certain criteria to ensure the continuation of sustainable and competitive development. This research aims to explore the success factors of special financial institutions for MRL development. Data were collected through questionnaires survey from ninety-one respondents with expertise in MRL development. The data were analysed using SmatPLS 3 software for Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the significant value of the items studied. The results highlighted four aspects namely i) financial sources, ii) financial policies and procedures, iii) government support and iv) Islamic financial structure as significant success factors in the establishment of special financial institutions for development of MRL.